PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN JACKPOT DI WILAYAH KOTA MEDAN - Yudarwin Yudarwin; Sahat Martua Sn; Ruthea Nazara; Theresia Sipahutar (LPPM Universitas Ekasakti Padang, 2022)
Gambling is betting an amount of money where the winner gets the bet money, as a form of game that is profitable for the main participants, and also all kinds of bets where those involved are not directly involved in the competition, including all kinds of other bets. Gambling is one of the criminal acts in Indonesia that is very disturbing to the public and needs to be eradicated more deeply. Nowadays, jackpot gambling is very common. Where the players range from adults, teenagers and minors, to women. Gambling no longer looks at age and gender. What's more, there are those who make this jackpot gambling their main livelihood. Therefore, the author wants to discuss more deeply about jackpot gambling. The author would like to study further about the crime of jackpot gambling with the title Thesis: